Funciones del presente histórico en dos textos narrativos tradicionales costarricenses - Constenla Umaña, Adolfo (Universidad de Costa Rica, 2020)
The purpose of this article is to determine the funtions of the historical present in two traditional Costa Rican narrative texts. The analisis shows that there is not a single function of the historical present in these texts, but several, such as that which marks direct style, and that which contributes to the organization of the texts in chronological segments and to the characterization of its orientation component.